If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9n + -1) + 12 = -60 Reorder the terms: 2(-1 + 9n) + 12 = -60 (-1 * 2 + 9n * 2) + 12 = -60 (-2 + 18n) + 12 = -60 Reorder the terms: -2 + 12 + 18n = -60 Combine like terms: -2 + 12 = 10 10 + 18n = -60 Solving 10 + 18n = -60 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 18n = -60 + -10 Combine like terms: 10 + -10 = 0 0 + 18n = -60 + -10 18n = -60 + -10 Combine like terms: -60 + -10 = -70 18n = -70 Divide each side by '18'. n = -3.888888889 Simplifying n = -3.888888889
| 8x-5-2x-12=1 | | x+.20=402 | | y+2x=X^2+4 | | F(x)=cos^3(x^2) | | 11-7x=-25 | | F+24=8 | | 5(x+4)-x=4(x+5)-1 | | -4a+(4a-5)= | | 6x^3+11x=13 | | 1+cos(8x)=4sin(2x) | | y-3=x^2+2x | | 2+2=6-6(x+4)+7x | | 2x+3(x+5)=5(x-3) | | 5-3logx=4 | | 3x=10+4y | | (6-9i)(6+9i)= | | 6x+12=118 | | 3.79=p-0.07 | | 3.79=p-0.05 | | 5(x-9)-7(3x+6)=25 | | 5(x+9)-7(3x+6)=25 | | 1+3(2)+3x=19 | | S=24+4h | | 2y^2+24x=0 | | (5x-7)-5(7x-12)+7=0 | | -7/3=x | | 4x-7=-51 | | y-8(/2)=7 | | 9x+2=-10 | | 1/2a-1/2=1/4a-1 | | 0=-x^2+8x+128 | | X=3/7 |